2020
DOI: 10.3897/mycokeys.62.39699
|View full text |Cite
|
Sign up to set email alerts
|

Longistriata flava (Boletaceae, Basidiomycota) – a new monotypic sequestrate genus and species from Brazilian Atlantic Forest

Abstract: A new monotypic sequestrate genus, Longistriata is described based on collections from the Neotropical forest of Atlantic forest in Paraíba, Northeast Brazil – an area known for its high degree of endemism. The striking features of this new fungus are the hypogeous habit, the vivid yellow peridium in mature basidiomes, broadly ellipsoid basidiospores with a distinct wall that is ornamented with longitudinal striations and lageniform cystidia with rounded apices. Phylogenetic analysis, based on LSU and tef-1α r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Gomez & Singer and possibly with the sequestrate genus Carolinigaster M.E. Smith & S. Cruz [5,7,8,31,[37][38][39][40][41][42][43][44][45][46][47]. The former three genera, along with Austroboletus, have been accommodated in the subfamily Austroboletoideae G. Wu & Zhu L. Yang, as they cluster in an well-delimited grouping with respect to other lineages in the Boletaceae [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomez & Singer and possibly with the sequestrate genus Carolinigaster M.E. Smith & S. Cruz [5,7,8,31,[37][38][39][40][41][42][43][44][45][46][47]. The former three genera, along with Austroboletus, have been accommodated in the subfamily Austroboletoideae G. Wu & Zhu L. Yang, as they cluster in an well-delimited grouping with respect to other lineages in the Boletaceae [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the longstanding of Fistulinella, an unanimous taxonomic interpretation of the genus has never been reached [6,27,56]. From the phylogenetic perspective, Fistulinella is inferred to be related to Austroboletus, Mucilopilus, Veloporphyrellus, and apparently Carolinigaster [5,7,8,[37][38][39]43,[45][46][47] and it seems to occupy a sister position to the remainder of the Austroboletoideae [5,7,39,41,43,45,47]. On the other hand, preliminary molecular analyses suggested this genus to be polyphyletic [31,37] and accordingly an inclusive revision complemented by further sampling from different geographic regions aiming at a better understanding of its generic boundaries would be urgently needed, especially in relation to morphologically very close smooth-spored genera such as Mucilopilus and Ixechinus R. Heim ex R. Heim.…”
Section: Introductionmentioning
confidence: 99%
“…The former traditional taxonomy was based only on morphological characters. However, since molecular techniques and phylogenetic analyses have been developed and used as an advanced tool for the modern concepts in systematics and taxonomy, many genera, and species in Boletaceae have been recognized and described as new, e.g., [1][2][3] [4][5][6][7][8][9][10][11][12]. Five of those genera were described from tropical to subtropical Asia, where high fungal diversity has been reported, but yet, remains poorly known to science, e.g., [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent systematic studies have revealed a considerable number of sequestrate (i.e. truffle-like and secotioid) fungal lineages in the family that have evolved independently from boletoid mushrooms (e.g., Castellano et al 2016;Desjardin et al 2008Desjardin et al , 2009Lebel et al 2012aLebel et al , 2012bNuhn et al 2013;Orihara et al 2010Orihara et al , 2016aOrihara et al , 2016bOrihara and Smith 2017;Smith et al 2015Smith et al , 2018Sulzbacher et al 2020;Vadthanarat et al 2018;Wu et al 2016). Although many sequestrate genera in Boletaceae comprise one or a few species, the genus Octaviania (orthographic variant: Octavianina), which belongs to the subfamily Leccinoideae (Wu et al 2014), is exceptionally diverse and includes more than 25 truffle-like species (Orihara et al 2012a;Paz et al 2014Paz et al , 2016.…”
Section: Introductionmentioning
confidence: 99%